Prevalence of viral load suppression, predictors of virological failure and patterns of HIV drug resistance after 12 and 48 months on first-line antiretroviral therapy: a national cross-sectional survey in Uganda. (5th February 2020) - Ssemwanga, Deogratius; Asio, Juliet; Watera, Christine; Nannyonjo, Maria; Nassolo, Faridah; Lunkuse, Sandra; Salazar-Gonzalez, Jesus F; Salazar, Maria G; Sanyu, Grace; Lutalo, Tom; Kabuga, Usher; Ssewanyana, Isaac; et al.
Abstract: Objectives: We implemented the WHO cross-sectional survey protocol to determine rates of HIV viral load (VL) suppression (VLS), and weighted prevalence, predictors and patterns of acquired drug resistance (ADR) in individuals with virological failure (VF) defined as VL ≥1000 copies/mL. Methods: We enrolled 547 and 1064 adult participants on first-line ART for 12 (±3) months (ADR12) and ≥48 months (ADR48), respectively. Dried blood spots and plasma specimens were collected for VL testing and genotyping among the VFs. Results: VLS was 95.0% (95% CI 93.4%–96.5%) in the ADR12 group and 87.9% (95% CI 85.0%–90.9%) in the ADR48 group. The weighted prevalence of ADR was 96.1% (95% CI 72.9%–99.6%) in the ADR12 and 90.4% (95% CI 73.6–96.8%) in the ADR48 group, out of the 30 and 95 successful genotypes in the respective groups. Initiation on a zidovudine-based regimen compared with a tenofovir-based regimen was significantly associated with VF in the ADR48 group; adjusted OR (AOR) 1.96 (95% CI 1.13–3.39). Independent predictors of ADR in the ADR48 group were initiation on a zidovudine-based regimen compared with tenofovir-based regimens, AOR 3.16 (95% CI 1.34–7.46) and ART duration of ≥82 months compared with <82 months, AOR 1.92 (95% CI 1.03–3.59). Conclusions: While good VLS was observed, the high prevalence of ADR among the VFs before they underwent the recommended three intensive adherence counselling (IAC) sessions followed by repeat VL testing implies that IAC prior to treatment switching may be of limited benefit in improving VLS.